The formation pathway of flavor compounds in steamed Antarctic krill (Euphausia superba) based on untargeted metabolomics - Tingting Yang; Yang Liu; Jing Bai; Yan Fan; Ye Chen; Ping Dong; Xia Yang; Hu Hou (Food Chemistry: X)
This study investigated the impact of steaming on the flavor and metabolic profile of Antarctic krill, aiming to elucidate the pathways responsible for flavor development and metabolic shifts during processing. HS-SPME-GC–MS identified key volatile compounds, including alcohols, aldehydes, ketones and so on. The results demonstrated a significant increase in nonanal content from 2.23 ± 0.06 μg/kg to 8.14 ± 1.26 μg/kg after steaming. The formation pathways of two key flavor compounds, nonanal and 1-octen-3-ol, were attributed to fatty acid degradation. Hierarchical clustering and volcano plot showed metabolic shifts between raw and steamed krill, with differential metabolites like hydroquinone and gamma-aminobutyric acid emerging as key contributors to flavor changes. Furthermore, metabolic network further linked these shifts to reactions involving amino acids, nucleotide and other compounds during steaming, impacting the overall taste.